2019
DOI: 10.1016/j.nmni.2019.100536
|View full text |Cite
|
Sign up to set email alerts
|

Virologic study of acute lower respiratory tract infections in children admitted to the paediatric department of Blida University Hospital, Algeria

Abstract: Acute lower respiratory tract infections (ALRTI) such as pneumonia and bronchiolitis are major causes of mortality and morbidity in children under 5 years of age. The main microbial agents responsible for ALRTI are either bacterial agents ( Streptococcus pneumoniae, Haemophilus influenzae type b, Mycoplasma pneumoniae ) or viruses (respiratory syncytial virus (RSV, also known as human orthopneumovirus), Myxovirus influenzae, Myxovirus parainfluenzae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…However, 14.8% of strains remained un-typeable [80]. A similar pattern was observed in Algeria in 2010, in which Derar et al reported a higher prevalence of RSV B (82%) [81]. Nevertheless, in the RSV outbreak of 2013-2015 in Saudi Arabia, a similar pattern was observed Egypt and Iraq [82][83][84].…”
Section: Rsv Subgroup and Strains Circulating In The Mena Regionsupporting
confidence: 60%
“…However, 14.8% of strains remained un-typeable [80]. A similar pattern was observed in Algeria in 2010, in which Derar et al reported a higher prevalence of RSV B (82%) [81]. Nevertheless, in the RSV outbreak of 2013-2015 in Saudi Arabia, a similar pattern was observed Egypt and Iraq [82][83][84].…”
Section: Rsv Subgroup and Strains Circulating In The Mena Regionsupporting
confidence: 60%
“…The pathophysiology behind dual viral infections can explain some of the epidemiology of viral-viral co-infections seen at the population level. Given the high rates of RSV and rhinovirus infections, it makes sense that they are the most commonly identified viruses in co-infected patients across multiple studies [14,[49][50][51][52][53][54][55]. However, one study did conclude that the odds of rhinovirus detection were lower when RSV was present and the odds of rhinovirus were significantly higher in those patients who received RSV immunoprophylaxis [56].…”
Section: Epidemiology Of Viral-viral Co-infectionsmentioning
confidence: 99%
“…ALRTI is still a significant cause of mortality in children below 5 years old and is responsible for 11% of deaths from all causes in this age group (4). In our study, mortality occurred in 1.7% of patients admitted to the hospital due to ALRTI.…”
Section: Discussionmentioning
confidence: 47%
“…Acute lower respiratory tract infection (ALRTI) presenting as pneumonia or acute bronchiolitis is the most frequent cause of hospitalization in infants below 2 years old worldwide (1)(2)(3). The etiology of ALRTI in infants may be either bacterial (Streptococcus pneumoniae, Haemophilus influenzae type b, Mycoplasma pneumonia) or viral (respiratory syncytial virus (RSV), influenza, parainfluenza, adenovirus, rhinovirus, human metapneumovirus (HMPV), coronavirus or bocavirus) (4,5). Viruses cause the majority of these childhood respiratory infections and are associated with significant morbidity and mortality, especially in developing countries (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%